The religious world of the Lord’s Prayer - Black, C. Clifton 1955- (2021)
The prayer Jesus taught his disciples to pray (Matt 6:9–13 = Luke 11:2–4) did not arise in a religious vacuum. A cursory study of Greek, Hebraic, Roman, and Hellenistic Jewish prayers exhibits important convergences with, and divergences from, the Lord’s Prayer.
Keywords: Prayer; Lord’s Prayer; Hebraic and Hellenistic Jewish Prayer; Greco-Roman Prayer